MODEL ELECTRONIC WORD OF MOUTH DALAM PENCIPTAAN E-PURCHASE DECISION PADA MARKET PLACE DI INDONESIA (SURVEI KEPERILAKUAN PADA MASA COVID-19) - Citra Savitri, - (2022)
Government policies in handling the COVID-19 pandemic have had an impact on the economy of all countries, especially Indonesia. Although the development of e-commerce and the number of market places continues to increase, it is not able to compete with a number of online retailers at the Asian level. The purpose of this research to measure how influence of eWOM Information Quality, eWOM Information Credibility, attitude toward eWOM Information, eWOM Information Usefullness, eWOM Information adaption, e-purchase decision at market place in Indonesia. This study used a descriptive verifikatif method with statistical data analysis using Structural Equation Modeling (SEM) AMOS. The unit of analysis in this study is the buyer of fashion products in the market in Indonesia, female gender and marital status with a total of 460 respondents. The sampling technique used is proportional random sampling. The result of the study are in form of a model that has implications for increasing e-purchase decision positif and significantly. The novelty of this research is the discovery of a electronic word of mouth model in increasing e-purchase decision and the result of empirical test that eWOM Quality, eWOM Information Credibility and attitude toward eWOM Information through the intervening variabel eWOM Information Usefullness have a significant effect. Improvement through eWOM information Usefulness and eWOM Information Adaption is supporting element for business to improving e-purchase decision